Produksi Hidrolisat Protein Kacang Koro Benguk dengan Aktivitas Penghambat Kerja Enzim Pengkonversi Angiotensin melalui Kombinasi Fermentasi dan Hidrolisis Enzimatik - Tesy Pratami; Azis Boing Sitanggang; Christofora Hanny Wijaya (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Mucuna bean (Mucuna pruriens L.) is a legume having high protein content which has the potential as a source of bioactive peptides. One of the bioactive peptides is an angiotensin-converting enzyme (ACE) inhibitor, thus, mucuna beans might be used as a potential source of antihypertensive compounds. This study aimed to increase the functionality of proteins from mucuna beans as ACE inhibitors using a combination of fermentation and enzymatic hydrolysis followed by membrane filtration. The mucuna beans were fermented for 0, 24, 48, 96, and 144 h. The highest ACE inhibitory activity of 54.37%, was obtained by fermentation of the beans at 48 h, with a protein content of 20.82 mg/mL. The 48 h fermented mucuna beans were further hydrolyzed using alcalase or neutrase and subsequently filtered with UF membranes having 20,10 and 5 kDa cut-off. The enzymatic hydrolysis followed by membrane filtration increased the ACE inhibitory activity of mucuna beans. The neutrase hydrolysates resulting from 5 kDa membrane filtration showed the best ACE inhibitory activity (62.96% with a protein content of 10.39 mg/mL). A combination of fermentation and enzymatic hydrolysis followed by filtration using UF-membrane was able to produce ACE inhibitory peptides from mucuna beans. The potential of mucuna beans peptides as ACE inhibitors was due to the presence of negatively charged amino acid residues such as Asp and Glu, positively charged amino acids such as Arg and Lys, and hydrophobic amino acids such as Val, Leu, Ala, and Ile.